Effect of scheduling of irrigation on yield and economics of safflower genotypesunder limited water availability conditions: Effect of scheduling of irrigation on yield and economics of safflower genotypesunder limited water availability conditions - C SUDHAKAR; C SUDHA RANI; T RAJESHWAR REDDY; C MANIKYA MINNIE; K KIRAN KUMAR REDDY (Journal of Oilseeds Research, 2023)
A field experiment was carried out to find out the effect of irrigation schedules for a suitable variety of safflower (Carthamus tinctorius L.) using 3 genotypes and seven irrigation schedules.. The seed yield of safflower was significantly influenced by safflower genotypes. The seed yield of safflower was significantly higher in DSH 184 (1253 kg /ha) which was followed by TSF-1 (1123 kg /ha). While NARI-6 recorded the lowest yields (972 kg /ha). The seed yield of safflower differed significantly due to the application of irrigation at critical stages of the crop. The crop received 3 irrigations each at the Stem elongation stage + Early flowering stage + Seed filling stage resulting in significantly superior yields (1489 kg/ha) which was followed by 2 irrigations each at the Stem elongation stage + Early flowering stage (1408 kg/ha) and 2 irrigations each at the Stem elongation stage + Seed filling stage (1303 kg/ha). Crop grown completely under rainfed conditions recorded the lowest yield (776 kg/ha). The seed yield increased up to 47.88% by providing 3 irrigations each at Stem elongation, Early flowering and Seed filling stages as compared to rainfed conditions.